Research progress in high-temperature corrosion of Ni-base alloys in coal ash/flue gas - DU Lingxiao; DING Hang; XIE Yun (Cailiao gongcheng)
To meet the requirements of green， efficient， and low-carbon development， the next generation of 700 ℃ level advanced ultra-supercritical （A-USC） coal-fired power plants with increased steam temperature and pressure has received great attention worldwide. However， the increased steam parameters and harsh service environment corresponding to the A-USC boiler seriously threaten the safe operation of heat-exchanging components. The traditional ferritic/martensitic heat-resistant steels and austenitic stainless steels cannot survive due to their inadequate creep strength and corrosion resistance at temperatures above 700 ℃， and Ni-base alloys are required. Based on the coal ash/flue gas environment related to A-USC boiler adopting oxy-fuel combustion， the research progress in high-temperature corrosion of Ni-base alloys exposed to flue gas and coal ash was summarized， especially focusing on the effect of corrosive CO2， H2O（g）， SO2 gases and sulfate salts on the thermal growth of CrO3 protective film on Ni-base alloys. Finally， the effect of oxide particulates in coal ash， Cl-containing gases， and molten KCl salts resulting from biomass combustion on the high-temperature corrosion behavior of Ni-base alloys is the key direction for future research.